Bioavailable testosterone is associated with symptoms of depression in adult men. Issue 8 (August 2020) - Chen, Zhongbao; Shen, Xubo; Tian, Kunming; Liu, Yijun; Xiong, Shimin; Yu, Qin; Dai, Lulu; Shi, Yongjun; Zhang, Renjuan; Zeng, Rong; Wan, Qiyou; Xiong, Chengliang; et al.
Objective: This study aimed to determine the relationship between serum testosterone levels and depressive symptoms in an adult male population. Methods: We conducted a cross-sectional study of 1166 male participants from Zunyi, Guizhou, China. Each participant completed a questionnaire, a brief clinical exam, and had a fasting blood sample taken. We measured serum testosterone, sex hormone-binding globulin, and luteinizing hormone levels. Multiple linear regression was used to evaluate the effect of demographic factors on the relationship between the depressive symptom score and serum sex hormone levels. Results: Mean testosterone, sex hormone-binding globulin, and luteinizing hormone levels were significantly higher in the depressive symptom group than in the non-depressed group. The mean calculated free serum testosterone level and free testosterone index (FTI) were significantly lower in the depressive symptom group than in the non-depressed group. Additionally, the mean FTI was significantly negatively correlated with the Beck Depression Inventory scale score in the multiple linear regression model (95% confidence interval: −3.274 to −0.406). Conclusions: Decreased bioactive testosterone levels might be a contributing factor of depression in adult men. The FTI could be the most sensitive biomarker reflecting the level of bioavailable testosterone in patients with depression.